Recent advancement in bioeffect, metabolism, stability, and delivery systems of apigenin, a natural flavonoid compound: challenges and perspectives - Chen, Peng; Chen, Fuchao; Guo, ZhiLei; Lei, Jiexin; Zhou, Benhong (Frontiers in Nutrition, 2023)
Apigenin is a bioflavonoid compound that is widely present in dietary plant foods and possesses biological activities that protect against immune, cardiovascular, and neurodegenerative diseases and cancer. Therefore, apigenin is widely used in food and medicine, and increasing attention has been drawn to developing new delivery systems for apigenin. This review highlights the biological effects, metabolism, stability, and bioactivity of apigenin. In addition, we summarized advancements in the delivery of apigenin, which provides some references for its widespread use in food and medicine. Better stability of apigenin may enhance digestion and absorption and provide health benefits. Constructing delivery systems (such as emulsions, nanostructured lipid carriers, hydrogels, and liposomes) for apigenin is an effective strategy to improve its bioavailability, but more animal and cell experiments are needed to verify these findings. Developing apigenin delivery systems for food commercialization is still challenging, and further research is needed to promote their in-depth development and utilization.